Chemical Reaction of Waterproofing Admixtures on the Corrosion Behaviour of Reinforced Cement Concrete - Geetha, A.; Perumal, P. (Asian Journal of Chemistry, 2011)
This paper deals about the corrosion behaviour of reinforced cement concrete using waterproofing admixtures. This addition of waterproofing admixtures turns concrete into a construction material in harmony with sustainable building development. The addition of waterproofing chemicals also increases the various strength of concrete. These studies were carried out by conducting accelerated corrosion test over the concrete specimen with and without chemicals for various dosages and curing period of 28 days. The cubical specimens of size 150 mm × 150 mm × 150 mm have been taken for this test. The contribution of waterproofing admixtures was found more in the corrosion behaviour of reinforced cement concrete since it reduces the permeability and improves the corrosion resistance.